Reframing the debate: A question of probability, not of likelihood ratio. Issue 5 (September 2016) - Biedermann, A.; Bozza, S.; Taroni, F.; Aitken, C.
Abstract: Evidential value is measured by a likelihood ratio. This ratio has two components, the probability, or probability density, of the evidence if the prosecution proposition is true and the probability (density) of the evidence if the defence proposition is true. It takes the form of a single value, even if these probabilities are subjective measures of belief of the reporting forensic scientist.